On zeros of functions of given proximate formal order analytic in a half-plane - Vynnyts’kyi, B. V.; Sharan, V.L. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We describe sequences of zeros of functionsf≢0 that are analytic in the half-plane ℂ+={z:Rez> and satisfy the condition $$\forall ε > 0\exists c_1 \in (0; + ∞ )\forall z \in \mathbb{C}_{\text{ + }} :\left| {f(z)} \right| \leqslant c_1 \exp \left( {(σ + ε )\left| z \right|η (\left| z \right|)} \right)$$ where 0≤σ